From Manual to Digital: The Evolution of E-Service Models in Public Administration - Wirjatmi, Endang; Abdullah, Sait; Dwiputrianti, Septiana; Wahyu Purwasto, Bambang; Sufianti, Ely (Indonesian Association for Public Administration (IAPA), 2024)
This study aims to develop an adaptive e-service-based public service model in North Cimahi District. Utilizing a multi-methodological approach, primarily the Soft System Methodology (SSM), the research encompasses document studies, surveys, interviews, and focus group discussions. The findings indicate that the implemented e-services significantly enhance service effectiveness but still need optimal efficiency or sufficient user and operator confidence. A proposed model emphasizes the acceleration of e-service development compatible with smartphones, fostering user independence and active public participation. Additionally, integrating various service applications, including electronic signature systems, is necessary to enhance data security. This integration is expected to reduce direct face-to-face interactions, improving ethical behavior and professionalism among service providers and increasing efficiency for the community and the government. Limitations include comprehensive public engagement and full integration of service applications. Practical implications suggest that e-services can streamline administrative processes and improve public trust in government institutions. Socially, the model promotes inclusivity and transparency in public service delivery. The originality of this study lies in its application of SSM to develop a responsive e-service model tailored to community needs in the context of local government services.